PENGARUH STORE ATMOSPHERE, KUALITAS PELAYANAN, GAYA HIDUP DAN TEMAN BERBELANJA TERHADAP KEPUTUSAN PEMBELIAN IMPILSIF (Studi Kasus Konsumen Distro Three Second Malang) - Rivaldi C Lengam; Rois Arifin; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT Research in the aims to find out the influence Store Atmosphere, Service Sample so fon amount of Quality, Lifestyle and Friends Shopping on the Decision of Purchasing Impulsive100 people who are consumers of Distro Three Second Malang. The method used in the analysis of descriptive analysis is to use validity, reliability, normality, multiple linear regressionanalysis, multicollinearity test, heteroscedasticity testing, hypothesis testing, and hypothesis testing. The this results of study in dicate that Variables Store Shopping, while partially each of Store Atmosphere, Variables Atmosphere ,Quality of Service, Lifestyle and Friends Quality of Service, Lifestyle and Friends of Cooperation Affecting the same effect on Purchasing Decisions Impulsive in Distro Three Second. Keywords: StoreAtmosphere, Service Quality, Lifestyle, Shopping Friends, Impulsive Purchasing Decisions